99mTc-TRODAT-1 SPECT/CT imaging as a complementary biomarker in the diagnosis of parkinsonian syndromes. Issue 4 (April 2018) - Mittal, Bhagwant R.; Sood, Apurva; Shukla, Jaya; Vatsa, Rakhee; Bhusari, Priya; Shree, Ritu; Mehta, Sahil; Goyal, Manoj; Modi, Manish
Abstract : Introduction: Parkinson's disease (PD) and Parkinson plus syndromes (PPS) are neurodegenerative movement disorders caused by loss of dopamine in the basal ganglia. The diagnosis of both PD and PPS is complex as it is made solely on the basis of clinical features, with no established imaging modality to aid in the diagnosis. Technetium-99m-labeled tropane derivative ( 99m Tc-TRODAT-1) binds to the dopamine transporters present in the presynaptic membrane of the dopaminergic nerve terminal. The aim of this prospective study was to investigate the potential usefulness of 99m Tc-TRODAT-1 imaging in the diagnosis of PD and PPS. Patients and methods: Fifty-eight patients with a clinical diagnosis of idiopathic PD or PPS were recruited. The severity of the disease was assessed using the Hoehn and Yahr scale. Patients in stage I and II were considered as cases of Early PD. Twenty-five apparently healthy volunteers served as controls. Brain single-photon emission computed tomography/computed tomography in all the participants was performed 3–4 h after an injection of 99m Tc-TRODAT-1. Specific uptake ratios (SURs) of striatum were calculated for both the left and right striatum, and the values were compared between PD, PPS, and healthy volunteers. Results: A significant lower uptake of tracer activity was found in either of the striatum in PD and PPS cases compared with the control group, which showed a symmetrical comma-shaped striatal uptake. This was also reflected in the SUR values, which were significantly higher in the control group in comparison with the PD and PPS patients ( P <0.001). A significant difference was also found in the SUR values between the cases of early PD and control group ( P <0.001).No significant difference was noted among the SUR values in different Hoehn and Yahr stages. Conclusion: For clinical practice, both the visual analysis and the quantitative parameters of 99m Tc-TRODAT-1 single-photon emission computed tomography/computed tomography showed usefulness in distinguishing cases of PD and PPS from the healthy individuals.